2004
DOI: 10.1590/s1413-81232004000400020
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da qualidade da formação: contribuição à discussão na área da saúde coletiva

Abstract: Visando contribuir com a discussão da implantação e implementação de mecanismos de avaliação de qualidade da formação na área da saúde coletiva, são abordadas neste artigo as principais características de processos de avaliação educacional a partir de alguns autores que tomam por base o conceito de qualidade. Entende-se ser necessária a criação de instrumentos de avaliação em todos os níveis da educação e que os instrumentos de avaliação das instituições de ensino devam ser calcados em princípios determinados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In a previous article (Hortale et al, 2004), quality was interpreted, as proposed by Royero (2003, p. 2), as "a fundamental category for conducting the assessment of the world's institutions of higher learning", highlighting its attributes as: (a) multidimensional and complex, encompassing educational and social processes; (b) a socially determined category, related to specific socioeconomic contexts; (c) associated with the on-going transformation and adaptation of educational systems; and (d) integrated with the process of social efficiency in institutions of higher learning. Based on the above definition, we observed that in the Argentine case, CONEAU has the responsibility of both assessing and accrediting the courses, using similar criteria to those of quality attributes.…”
Section: Final Remarksmentioning
confidence: 93%
See 1 more Smart Citation
“…In a previous article (Hortale et al, 2004), quality was interpreted, as proposed by Royero (2003, p. 2), as "a fundamental category for conducting the assessment of the world's institutions of higher learning", highlighting its attributes as: (a) multidimensional and complex, encompassing educational and social processes; (b) a socially determined category, related to specific socioeconomic contexts; (c) associated with the on-going transformation and adaptation of educational systems; and (d) integrated with the process of social efficiency in institutions of higher learning. Based on the above definition, we observed that in the Argentine case, CONEAU has the responsibility of both assessing and accrediting the courses, using similar criteria to those of quality attributes.…”
Section: Final Remarksmentioning
confidence: 93%
“…In Latin America, during the 1990s, proposals for reform in health and higher education were part of an overall regional arrangement for public policies in this area, with financial support and strategic monitoring by institutions like the WB and IDB (Hortale et al, 2004). The quality assessment models implemented in higher education varied from country to country, but adopting similar logics to the four models described previously.…”
Section: Reforms In Higher Educations: the Impacts On Training In Heamentioning
confidence: 99%